(untitled) (Development Service Industry Management, 2025)
The paper examines the theoretical foundations of business promotion in the digital environment within the framework of strategic management. Based on the research findings, it synthesizes the key distinctions between the concepts of “promotion” and “marketing communications”, clarifies the definition of the promotion mix as an economic category, and identifies its main components, as well as indicates specific features of business promotion in the digital space. It is substantiated that the selection of digital channels and tools for promoting a company’s products and services should be carried out with consideration of the business’s specific characteristics, the product life cycle stage, the business objectives, and the prevailing market conditions. The classification of digital promotion channels has been expanded based on the criterion of ownership and control, which implies a division into owned, paid (external), and earned channels within the operational context of contemporary business organizations. It examines the characteristics of business promotion tools in the digital environment within these categories, and generalizes the key factors for their effective implementation. It can be concluded that the prerequisite for effective digital promotion of a brand, product, or service is the integration of these types of channels through a coherent promotion strategy supported by analytics and process automation.